A finite element modeling study of peripheral nerve recruitment by percutaneous tibial nerve stimulation in the human lower leg. (March 2018) - Elder, Christopher W.; Yoo, Paul B.
Highlights: Constructed for the first time a finite element model of percutaneous tibial nerve stimulation (PTNS) in a human leg. Demonstrated co-activation of the saphenous nerve branches during PTNS. Supports the idea that activation of saphenous nerve afferents contribute to the effects of PTNS therapy. Abstract: Percutaneous tibial nerve stimulation (PTNS) is a clinical therapy for treating overactive bladder (OAB), where an un-insulated stainless steel needle electrode is used to target electrically the tibial nerve (TN) in the lower leg. Recent studies in anesthetized animals not only confirm that bladder-inhibitory reflexes can be evoked by stimulating the TN, but this reflex can also be evoked by stimulating the adjacent saphenous nerve (SAFN). Although cadaver studies indicate that the TN and major SAFN branch(es) overlap at the location of stimulation, the extent to which SAFN branches are co-activated is unknown. In this study, we constructed a finite element model of the human lower leg and applied a numeric axon model (MRG model) to simulate the electrical recruitment of TN and SAFN fibers during PTNS. The model showed that up to 80% of SAFN fibers (located at the level of the needle electrode) can be co-activated when electrical pulses are applied at the TN activation threshold, the standard therapeutic amplitude. Both the location of the inserted electrode and stimulation amplitude were important variables that affected the recruitment of SAFN branches. This study suggests further work is needed to investigate the potential therapeutic effects of SAFN stimulation in OAB patients.